(3cJGH GdMjOIs - (3YHO GdYRjR Hf jMji Hf eSde Hf ejehf GdcfGfj Gdecjs ((3YHO GdYRjR Hf YHO Gddg Hf YGeQ Hf YHO Gddg Hf YGeQ s)
(3ChdgG (B:s
(3bGd YHO GdYRjR Hf jMji EJUd Hi hCfG Hecg eG bO CXgQg HTQ Hf ZjGK GdeQjSi ef Gdbhd HNda GdbQBf hZjQg hOYGFg GdfGS Edi ehGabJg Ydi bhdg hePgHg s
(3BNQgG (B:s
(3bdJ CfG CPcQ dce HYV eG LQi eeG dGjLhR Ydi ajg TF hdG MLI ai PcQg aQVhG HPdc efi gPG cdg deG JNhaJ Ydi faSi eeG bO dMbfi HYO gPG GdeLdS heG LQg HSHH GdChQGb GdJi CedjJgG Ydi GdfGS hcJHhgG Yfi ai cJGH ZjQ gPG Je cJGH GdMjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3HChdg JQLeI ddeUfas
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds